2018
DOI: 10.1021/jacs.7b11463
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Kinetic Modeling Reveals an Ensemble of Cl/H+ Exchange Pathways in ClC-ec1 Antiporter

Abstract: Despite several years of research, the ion exchange mechanisms in chloride/proton antiporters and many other coupled transporters are not yet understood at the molecular level. Here, we present a novel approach to kinetic modeling and apply it to ion exchange in ClC-ec1. Our multiscale kinetic model is developed by (1) calculating the state-to-state rate coefficients with reactive and polarizable molecular dynamics simulations, (2) optimizing these rates in a global kinetic network, and (3) predicting new elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 59 publications
6
76
0
Order By: Relevance
“…This proposal appears harmonious with the 30 hydrophobic nature of the protein core explored by the Glu in side chain and the fact that other CLC 31 homologs use neutral residues at this position (Feng et al, 2010;Phillips et al, 2012;Stockbridge et 1 al., 2012). In addition, the proposal is consistent with MD simulations that show the Glu ex /Glu in doubly 2 protonated state is highly populated (Mayes et al, 2018) and can favor formation of water pathways 3 under certain conditions (Ko and Jo, 2010). Nevertheless, simulations with glutamate side chains in 4 the QQQ conformational state, together with explicit evaluation of H + transport (Wang et al, 2018;5 Duster et al, 2019), are needed to elaborate details of the H + -transfer steps.…”
Section: Discussion 29supporting
confidence: 64%
See 2 more Smart Citations
“…This proposal appears harmonious with the 30 hydrophobic nature of the protein core explored by the Glu in side chain and the fact that other CLC 31 homologs use neutral residues at this position (Feng et al, 2010;Phillips et al, 2012;Stockbridge et 1 al., 2012). In addition, the proposal is consistent with MD simulations that show the Glu ex /Glu in doubly 2 protonated state is highly populated (Mayes et al, 2018) and can favor formation of water pathways 3 under certain conditions (Ko and Jo, 2010). Nevertheless, simulations with glutamate side chains in 4 the QQQ conformational state, together with explicit evaluation of H + transport (Wang et al, 2018;5 Duster et al, 2019), are needed to elaborate details of the H + -transfer steps.…”
Section: Discussion 29supporting
confidence: 64%
“…One proposal is 7 that the inner-gate area remains static and transport works via a kinetic barrier to Clmovement to 8 and from the intracellular side (Feng et al, 2010). Consistent with this proposal, multiscale kinetic 9 modeling revealed that 2:1 Cl -/H + exchange can arise from kinetic coupling alone, without the need 10 for large protein conformational change (Mayes et al, 2018). An alternative proposal is that CLCs 11 visit a conformationally distinct inward-open state, based on the finding that transport activity is 12 inhibited by cross-links that restrict motion of Helix O, located adjacent to the inner gate (Basilio et 13 al., 2014;Accardi, 2015).…”
Section: Discussion 29mentioning
confidence: 92%
See 1 more Smart Citation
“…One proposal is that the inner-gate area remains static and transport works via a kinetic barrier to Clmovement to and from the intracellular side (Feng et al, 2010). Consistent with this proposal, multiscale kinetic modeling revealed that 2:1 Cl -/H + exchange can arise from kinetic coupling alone, without the need for large protein conformational change (Mayes et al, 2018). An alternative proposal is that CLCs visit a conformationally distinct inward-open state, based on the finding that transport activity is inhibited by cross-links that restrict motion of Helix O, located adjacent to the inner gate (Basilio et al, 2014;Accardi, 2015).…”
Section: A Proposed Unifying Framework For the Clc Transport Mechanismmentioning
confidence: 85%
“…However, MD simulations revealed that Gln in is highly dynamic and most often is rotated away from its starting position, allowing the robust formation of water pathways from the intracellular bulk water directly to Gln ex (Figure 8) (State E). Once such transfer occurs, the deprotonated Glu ex will be disfavored in the hydrophobic core, and it will compete with Clfor the S cen anion-binding site, generating State F. Although this conformational state has not been observed crystallographically for CLC-ec1, computational studies found that Glu ex favors the S cen position when there are no Clions bound in the pathway (as in State F), (Picollo et al, 2012) and that the "down" position is in general the preferred orientation for Glu ex (Mayes et al, 2018). In addition, a recent structure of an Asp ex CLC-ec1 mutant supports that the carboxylate likes to reach down towards S cen , in a "midlow" position, excluding the presence of Clat both S cen and S ext (Park et al, 2019), as depicted in State F. From this state, binding of Clfrom the intracellular side (coordinated with inner-gate opening (Basilio et al, 2014)) knocks Glu ex back up to S ext , generating the original state A.…”
Section: A Proposed Unifying Framework For the Clc Transport Mechanismmentioning
confidence: 97%